Synthesis, characterization and drug delivery application of Dapsone based double tailed biocompatible nonionic surfactant. (September 2021) - Gul, Jasra; ullah, Shafi; Ali, Imdad; Rao, Komal; Iqbal, Kanwal Muhammad; Jabri, Tooba; Perveen, Samina; Rashid, Abdur; Shah, Muhammad Raza
Highlights: Dapsone based nonionic surfactant has been synthesized and characterized. The synthesized surfactant is biocompatible and non-toxic. It can encapsulate high amount of ceftriaxone and release it in sustained manner. Drug loaded vesicles showed higher antibacterial and ant biofilm activity. The synthesized surfactant can potentially be used for drug delivery. Abstract: The increase in antimicrobial resistance has created a crisis that has become top priority for global policy and public health. Antibiotics are constantly being rendered in-effective due to the emergence of bacterial resistance; therefore, novel strategies for improving therapeutic efficacies of existing drugs must be focused. Advancements in nanotechnology have opened up new avenues for enhancing therapeutic efficacy of existing drugs via construction of intelligent and efficient delivery systems. This study reports the synthesis of Dapsone based nonionic surfactant and its utilization as delivery system for Ceftriaxone sodium. The synthesized nonionic surfactant was characterized via mass spectrometry and 1 H NMR and IR spectroscopic techniques. The drug loaded vesicles of newly synthesized sulfur based nonionic were formed through thin film hydration method and characterized for drug entrapment efficiency, vesicles size, zeta potential, morphology using UV–vis spectrometry, dynamic light scattering (DLS) and atomic force microscopic (AFM) techniques. The biocompatibility of newly synthesized surfactant was assessed using blood hemolysis and in-vitro cells cytotoxicity. Antibacterial potential of drug loaded vesicles was assessed in gram positive and gram negative bacterial cultures. The spectroscopic results confirm successful synthesis of novel sulfur based nonionic surfactant that formed spherical shaped drug loaded vesicles with an average size of 97.95 ± 3.45 nm and 56.3 ± 3.15 % entrapment of the model drug (Ceftriaxone sodium). The vesicles displayed negative surface charge of -16.8 ± 3.72 mV and released the entrapped drug in a controlled way in-vitro drug release. The drug loaded vesicular formulation showed enhanced cellular uptake and greater antibacterial potentials when compared with control. Results of this study show that the Dapsone based surfactant is safe, biocompatible, non-toxic and can be used as promising vesicular carrier for enhancing therapeutic efficacy of antibacterial drug, Ceftriaxone sodium.